2008
DOI: 10.1525/auk.2008.125.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Stress Responsiveness in Nestlings: A Comparison of Two Sampling Techniques

Abstract: I compared the effects on plasma corticosterone levels of two methods of collecting blood samples during standardized capture and handling stress protocols. In one method, individual nestling American Kestrels (Falco sparverius) were bled at three time periods: when initially removed from the nest, and 15 and 30 min later. In the other method, siblings removed from a nest were bled once each, either at the time of removal, or 15 or 30 min later. I found that there was no difference between the two groups in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Validity of responses to the language milestone questions was examined through assessment of the examples of first words and word combinations the parents provided in the case history forms. The observers were asked to rate acceptability of examples as true instances of first words or word combinations using a 5-point Likert-type scale (1 = totally unacceptable , 2 = unacceptable , 3 = neutral , 4 = acceptable , and 5 = perfectly acceptable ; adapted from Vagias, 2006). The median rating across the two observers was 5 for first words indicating that these examples were generally perfectly acceptable and 4 for first word combinations indicating that these examples were generally acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…Validity of responses to the language milestone questions was examined through assessment of the examples of first words and word combinations the parents provided in the case history forms. The observers were asked to rate acceptability of examples as true instances of first words or word combinations using a 5-point Likert-type scale (1 = totally unacceptable , 2 = unacceptable , 3 = neutral , 4 = acceptable , and 5 = perfectly acceptable ; adapted from Vagias, 2006). The median rating across the two observers was 5 for first words indicating that these examples were generally perfectly acceptable and 4 for first word combinations indicating that these examples were generally acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…On sampling days, nestlings were removed from nests and taken to an adjacent shady site to minimize stress of sampled nestlings and disturbance of local nests. Because blood samples could not be obtained in less than 3 min to achieve a baseline level of PCORT (Romero & Reed 2005), we standardized holding time (5 min) for nestlings before sampling, recognizing that standard capture‐and‐handling stress protocols may in fact underestimate the stress response due to haemodilution (Duffy 2008). We collected up to 1 mL of blood from the brachial or jugular veins using a 27·5‐gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…We sampled stress-induced CORT at 15 min because previous research on juvenile kestrel CORT secretion patterns showed that most birds reached maximum CORT concentrations within 10-20 minutes [19,25]. We did not bleed the same birds twice to avoid underestimating CORT levels [15]. If a brood consisted of one nestling, we collected only baseline from this individual.…”
Section: Disturbance Protocolmentioning
confidence: 99%